1980
DOI: 10.1111/j.1365-2133.1980.tb15831.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of psoriasis: comparison of photochemotherapy and several variants of phototherapy

Abstract: Four treatments involving light were compared in two series of patients with severe psoriasis. The first series consisted of ten patients, who were treated by the method of paired comparisons. The treatments given were: (1) exposure to fluorescent sunlamps (B); (2) the same, supplemented by fluorescent UV-A lamps (A + B); (3) the same as (2) with the addition of the radiation from germicidal lamps (A + B + C); (4) photochemotherapy with oral 8-MOP followed by UV-A (PUVA); (5) one of the fields served as contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…In early 1980s, it was observed that the beneficial effect of UVB is mainly related to wavelengths between 295 and 313 nm, and a range between 310 and 313 nm seemed to have the best safety profile [9,10]. Consequently a lamp, emitting UVB irradiation with a peak at 311–312 nm (known as narrow-band ultraviolet B—NB-UVB) and excluding shorter, photobiologically more dangerous wavelengths, has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…In early 1980s, it was observed that the beneficial effect of UVB is mainly related to wavelengths between 295 and 313 nm, and a range between 310 and 313 nm seemed to have the best safety profile [9,10]. Consequently a lamp, emitting UVB irradiation with a peak at 311–312 nm (known as narrow-band ultraviolet B—NB-UVB) and excluding shorter, photobiologically more dangerous wavelengths, has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of recommendations for the treatment of psoriasis using topical and systemic PUVA is shown in Table IV. COMPARISON STUDIES BB-UVB compared with NB-UVB Several small, half body comparison studies have evaluated the efficacy of BB-UVB compared with NB-UVB therapy in the treatment of psoriasis and these small studies suggest that NB-UVB has improved efficacy when compared with BB-UVB therapy. 11,29,36,37,159 A randomized controlled trial of 100 patients demonstrated that NB-UVB was more likely to clear psoriasis compared with selective BB-UVB Once clearance has been achieved, maintenance treatment may or may not be used Remission times: 3-12 mo Contraindications:…”
Section: Contraindicationsmentioning
confidence: 98%
“…These systems have been found to possess mutagenic properties when applied in conjunction with near UV-A light (320-400 nm) exposure [5][6][7][17][18][19][20][21]. The treatment coined psoralen + UV-A (PUVA) therapy has been specifically designed to treat different skin disorders such as psoriasis and vitiligo [23][24][25][26]. The use of plants rich in furocoumarins constitutes a therapy known since many centuries ago that was employed in ancient India and Egypt to treat leukoderma and vitiligo [19].…”
Section: Introductionmentioning
confidence: 99%